Co‐occurring chronic pain and primary psychological disorders in adolescents: A scoping review - Sharon Bateman; Line Caes; Christopher Eccleston; Melanie Noel; Abbie Jordan (Wiley, 2023)
Abstract Long‐term health conditions, whether mental or physical, often co‐occur in adolescents. For instance, adolescents with chronic pain may experience co‐occurring primary psychological disorders. In this scoping review, we determine the influence of co‐occurring chronic pain and primary psychological disorders on adolescents' functioning. A systematic search of six databases was conducted to identify articles if they were: (1) peer‐reviewed; (2) reported original findings; (3) included participants aged 11-19 years, who experienced chronic pain (i.e., pain lasting 3 months or more) and had a co‐occurring diagnosis of a primary psychological disorder; and (4) assessed functioning. Searches returned 9864 articles after the removal of duplicates. A two‐phase abstract and full‐text screening process identified two eligible articles which compared emotional functioning (n = 1) and social functioning (n = 2) between groups of adolescents with co‐occurring chronic pain and primary psychological disorders with adolescents only reporting chronic pain. Overall findings revealed no differences in social functioning, but adolescents with co‐occurring chronic pain and a primary psychological disorder (depression and anxiety) reported worse emotional functioning compared with adolescents with chronic pain alone. This review confirms the limited research on the co‐occurrence of primary psychological disorders and chronic pain in adolescents by only identifying two eligible articles exploring the co‐occurrence of chronic pain with depression, anxiety, and/or attentional disorders.